India’s Effort to Join 21st-Century Higher Education - Altbach, Philip; Jayaram, N. (International Higher Education, 2009)
India is poised to invest into the creation of many new universities, toward the goal of having 30 "world-class" universities capable of competing on the global academic playing field. Many problems currently plague the Indian higher educational system (an underpaid professoriate, institutional corruption, lack of focus on research, etc.) and must be carefully examined and addressed before investments are made, or these lofty goals may not succeed.